Enhanced Photon–Phonon Interaction in WSe2 Acoustic Nanocavities - Carr, Alex D.; Ruppert, Claudia; Samusev, Anton K.; Magnabosco, Giulia; Vogel, Nicolas; Linnik, Tetiana L.; Rushforth, Andrew W.; Bayer, Manfred; Scherbakov, Alexey V.; Akimov, Andrey V. (ACS Photonics)

Coherent Phonons in van der Waals MoSe2/WSe2 Heterobilayers - Li, Changxiu; Scherbakov, Alexey V.; Soubelet, Pedro; Samusev, Anton K.; Ruppert, Claudia; Balakrishnan, Nilanthy; Gusev, Vitalyi E.; Stier, Andreas V.; Finley, Jonathan J.; Bayer, Manfred; Akimov, Andrey V. (Nano Letters)

Valence band electronic structure of the van der Waals antiferromagnet FePS3 - Nitschke, Jonah Elias; Esteras, Dorye L.; Gutnikov, Michael; Schiller, Karl; Mañas-Valero, Samuel; Coronado, Eugenio; Stupar, Matija; Zamborlini, Giovanni; Ponzoni, Stefano; Baldoví, José J.; Cinchetti, Mirko (Materials Today Electronics)

Remote epitaxy of In(x)Ga(1-x)As(001) on graphene covered GaAs(001) substrates - Henksmeier, Tobias; Schulz, Johann Friedemann; Kluth, Elias; Feneberg, Martin; Goldhahn, Rüdiger; Sanchez, Ana M.; Voigt, Markus; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)

Coherent Phononics of van der Waals Layers on Nanogratings - Akimov, Andrey V.; Barra-Burillo, María; Bayer, Manfred; Bradford, Jonathan; Gusev, Vitalyi E.; Hueso, Luis E.; Kent, Anthony; Kukhtaruk, Serhii; Nadzeyka, Achim; Patanè, Amalia; Rushforth, Andrew W.; Scherbakov, Alexey V.; et al. (Nano Letters)

Ultrafast All-Optical Polarization Switch Controlled by Optically Excited Picosecond Acoustic Perturbation of Exciton Resonance in Planar Microcavities - Demenev, A.A.; Yaremkevich, D.D.; Scherbakov, A.V.; Gavrilov, S.S.; Yakovlev, D.R.; Kulakovskii, V.D.; Bayer, M. (Physical Review Applied)

Selective Etching of (111)B-Oriented AlxGa1−xAs-Layers for Epitaxial Lift-Off - Henksmeier, Tobias; Eppinger, Martin; Reineke, Bernhard; Zentgraf, Thomas; Meier, Cedrik; Reuter, Dirk (physica status solidi (a))
GaAs-(111)-nanostructures exhibiting second harmonic generation are new building blocks in nonlinear optics. Such structures can be fabricated through epitaxial lift-off using selective etching of Al-containing layers and subsequent transfer to glass substrates. Herein, the selective etching of (111)B-oriented AlxGa1−xAs sacrificial layers (10–50 nm thick) with different aluminum concentrations (x = 0.5–1.0) in 10% hydrofluoric acid is investigated and compared with standard (100)-oriented structures. The thinner the sacrificial layer and the lower the aluminum content, the lower the lateral etch rate. For both orientations, the lateral etch rates are in the same order of magnitude, but some quantitative differences exist. Furthermore, the epitaxial lift-off, the transfer, and the nanopatterning of thin (111)B-oriented GaAs membranes are demonstrated. Atomic force microscopy and high-resolution X-ray diffraction measurements reveal the high structural quality of the transferred GaAs-(111) films.
Keywords: epitaxial lift-off; GaAs/AlxGa1−xAs heterostructures; selective etching

Extremely low-energy ARPES of quantum well states in cubic-GaN/AlN and GaAs/AlGaAs heterostructures - Hajlaoui, Mahdi; Ponzoni, Stefano; Deppe, Michael; Henksmeier, Tobias; As, Donat Josef; Reuter, Dirk; Zentgraf, Thomas; Springholz, Gunther; Schneider, Claus Michael; Cramm, Stefan; Cinchetti, Mirko (Scientific Reports)
Abstract Quantum well (QW) heterostructures have been extensively used for the realization of a wide range of optical and electronic devices. Exploiting their potential for further improvement and development requires a fundamental understanding of their electronic structure. So far, the most commonly used experimental techniques for this purpose have been all-optical spectroscopy methods that, however, are generally averaging in momentum space. Additional information can be gained by angle-resolved photoelectron spectroscopy (ARPES), which measures the electronic structure with momentum resolution. Here we report on the use of extremely low-energy ARPES (photon energy ~ 7 eV) to increase depth sensitivity and access buried QW states, located at 3 nm and 6 nm below the surface of cubic-GaN/AlN and GaAs/AlGaAs heterostructures, respectively. We find that the QW states in cubic-GaN/AlN can indeed be observed, but not their energy dispersion, because of the high surface roughness. The GaAs/AlGaAs QW states, on the other hand, are buried too deep to be detected by extremely low-energy ARPES. Since the sample surface is much flatter, the ARPES spectra of the GaAs/AlGaAs show distinct features in momentum space, which can be reconducted to the band structure of the topmost surface layer of the QW structure. Our results provide important information about the samples’ properties required to perform extremely low-energy ARPES experiments on electronic states buried in semiconductor heterostructures.

Protected Long-Distance Guiding of Hypersound Underneath a Nanocorrugated Surface - Yaremkevich, Dmytro D.; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Linnik, Tetiana L.; Khokhlov, Nikolay E.; Godejohann, Felix; Dyatlova, Olga A.; Nadzeyka, Achim; Pattnaik, Debi P.; Wang, Mu; Roy, Syamashree; Campion, Richard P.; et al. (ACS Nano)

Lifting restrictions on coherence loss when characterizing non-transparent hypersonic phononic crystals - Rolle, Konrad; Yaremkevich, Dmytro; Scherbakov, Alexey V.; Bayer, Manfred; Fytas, George (Nature Scientific Reports)

Picosecond ultrasonics with miniaturized semiconductor lasers - Kobecki, Michal; Tandoi, Giuseppe; Di Gaetano, Eugenio; Sorel, Marc; Scherbakov, Alexey V.; Czerniuk, Thomas; Schneider, Christian; Kamp, Martin; Höfling, Sven; Akimov, Andrey V.; Bayer, Manfred (Ultrasonics)

Ultrafast strain-induced switching of a bistable cavity-polariton system - Demenev, A.A.; Yaremkevich, D.D.; Scherbakov, A.V.; Kukhtaruk, S.M.; Gavrilov, S.S.; Yakolev, D.R.; Kulakovskii, V.D.; Bayer, M. (Physical Review B)

Stacked Self-Assembled Cubic GaN Quantum Dots Grown by Molecular Beam Epitaxy - Blumenthal, Sarah; Rieger, Torsten; Meertens, Doris; Pawlis, Alexander; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
We have investigated the stacking of self-assembled cubic GaN quantum dots (QDs) grown in Stranski–Krastanov (SK) growth mode. The number of stacked layers is varied to compare their optical properties. The growth is in situ controlled by reflection high energy electron diffraction to prove the SK QD growth. Atomic force and transmission electron microscopy show the existence of wetting layer and QDs with a diameter of about 10 nm and a height of about 2 nm. The QDs have a truncated pyramidal form and are vertically aligned in growth direction. Photoluminescence measurements show an increase of the intensity with increasing number of stacked QD layers. Furthermore, a systematic blue-shift of 120 meV is observed with increasing number of stacked QD layers. This blueshift derives from a decrease in the QD height, because the QD height has also been the main confining dimension in our QDs.
Keywords: cubic crystals; GaN; molecular beam epitaxy; quantum dots

Systematic study of the influence of coherent phonon wave packets on the lasing properties of a quantum dot ensemble - Wigger, Daniel; Czerniuk, Thomas; Reiter, Doris E; Bayer, Manfred; Kuhn, Tilmann (New Journal of Physics)
Coherent phonons can greatly vary light–matter interaction in semiconductor nanostructures placed inside an optical resonator on a picosecond time scale. For an ensemble of quantum dots (QDs) as active laser medium, phonons are able to induce a large enhancement or attenuation of the emission intensity, as has been recently demonstrated. The physics of this coupled phonon–exciton–light system consists of various effects, which in the experiment typically cannot be clearly separated, in particular, due to the complicated sample structure a rather complex strain pulse impinges on the QD ensemble. Here we present a comprehensive theoretical study how the laser emission is affected by phonon pulses of various shapes as well as by ensembles with different spectral distributions of the QDs. This gives insight into the fundamental interaction dynamics of the coupled phonon–exciton–light system, while it allows us to clearly discriminate between two prominent effects: the adiabatic shifting of the ensemble and the shaking effect. This paves the way to a tailored laser emission controlled by phonons.

Picosecond Control of Quantum Dot Laser Emission by Coherent Phonons - Czerniuk, T.; Wigger, D.; Akimov, A. V.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Kuhn, T.; Reiter, D. E.; Bayer, M. (Physical Review Letters)
A picosecond acoustic pulse can be used to control the lasing emission from semiconductor nanostructures by shifting their electronic transitions. When the active medium, here an ensemble of (In,Ga)As quantum dots, is shifted into or out of resonance with the cavity mode, a large enhancement or suppression of the lasing emission can dynamically be achieved. Most interesting, even in the case when gain medium and cavity mode are in resonance, we observe an enhancement of the lasing due to shaking by coherent phonons. In order to understand the interactions of the nonlinearly coupled photon-exciton-phonon subsystems, we develop a semiclassical model and find an excellent agreement between theory and experiment.

Acousto-optical nanoscopy of buried photonic nanostructures - Czerniuk, T.; Schneider, C.; Kamp, M.; Höfling, S.; Glavin, B. A.; Yakovlev, D. R.; Akimov, A. V.; Bayer, M. (Optica)
We develop a nanoscopy method with in-depth resolution for layered photonic devices. Photonics often requires tailored light field distributions for the optical modes used, and an exact knowledge of the geometry of a device is crucial to assess its performance. The presented acousto-optical nanoscopy method is based on the uniqueness of the light field distributions in photonic devices: for a given wavelength, we record the reflectivity modulation during the transit of a picosecond acoustic pulse. The temporal profile obtained can be linked to the internal light field distribution. From this information, a reverse-engineering procedure allows us to reconstruct the light field and the underlying photonic structure very precisely. We apply this method to the slow light mode of an AlAs/GaAs micropillar resonator and show its validity for the tailored experimental conditions.

Impact of nanomechanical resonances on lasing from electrically pumped quantum dot micropillars - Czerniuk, T.; Tepper, J.; Akimov, A. V.; Unsleber, S.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Bayer, M. (Applied Physics Letters)
We use a picosecond acoustics technique to modulate the laser output of electrically pumped GaAs/AlAs micropillar lasers with InGaAs quantum dots. The modulation of the emission wavelength takes place on the frequencies of the nanomechanical extensional and breathing (radial) modes of the micropillars. The amplitude of the modulation for various nanomechanical modes is different for every micropillar which is explained by a various elastic contact between the micropillar walls and polymer environment.